Keropok Pedas Crunchy / Muhammad Amirul Izham Mohd Nawawi - Mohd Nawawi, Muhammad Amirul Izham (2021)
This is basically a business report for a small business where my business name is Keropok Pedas Crunchy. This business open when I take subject of Principle of Entrepreneurship(ENT530) for this semester. In this subject, I must open my own business using Facebook page for the first starting business and this business have registration from Suruhanjaya Syarikat Malaysia (SSM). Registered location of my business at Kampung Air Merah, Batu Gajah 17410, Tanah Merah, Kelantan. There are a lot of knowledge that I learned and absorbed at the times given. According to my field of study, I was assigned to the media social assignment as a medium to me to gain knowledge in entrepreneur industry. This is because the subject that, I learn are very competitive and expose me to be good in selling items, innovate new items and sharpen my communication skills in order to improve myself. I learn a lot when Dr Zawani teach me this subject. She gave me an expose to this industry which I think I have found myself good at this field. Day by day, I started to improve myself thanks Dr Zawani. After four month I have learn there, I have totally improved myself from nothing to something. For start-up business typically one of the main goals of the business is to expend this business to another stage and lastly to introduce to the world. This business maybe does not have if not because of the subject I learn in this semester which is Principle of Entrepreneurship (ENT530). I hope this report will help for the person who want start their business just using Facebook and also help to continue my business even though I did not learn again this subject.